Hatching plasticity in the tropical gastropod Nerita scabricosta. Issue 2 (8th April 2016) - Collin, Rachel; Roof, Karah Erin; Spangler, Abby
Abstract: Hatching plasticity has been documented in diverse terrestrial and freshwater taxa, but in few marine invertebrates. Anecdotal observations over the last 80 years have suggested that intertidal neritid snails may produce encapsulated embryos able to significantly delay hatching. The cause for delays and the cues that trigger hatching are unknown, but temperature, salinity, and wave action have been suggested to play a role. We followed individual egg capsules of Nerita scabricosta in 16 tide pools to document the variation in natural time to hatching and to determine if large delays in hatching occur in the field. Hatching occurred after about 30 d and varied significantly among tide pools in the field. Average time to hatching in each pool was not correlated with presence of potential predators, temperature, salinity, or pool size. We also compared hatching time between egg capsules in the field to those kept in the laboratory at a constant temperature in motionless water, and to those kept in the laboratory with sudden daily water motion and temperature changes. There was no significant difference in the hatching rate between the two laboratory treatments, but capsules took, on average, twice as long to hatch in the laboratory as in the field. Observations of developing embryos showed that embryos in the field develop slowly and continuously until hatching, but embryos in the laboratory reach the hatching stage during the first month of development and remain in stasis after that. Instances of hatching plasticity in benthic marine invertebrates, like the one in N. scabricosta, could greatly enhance our ability to investigate the costs and benefits of benthic versus planktonic development, a long‐standing area of interest for invertebrate larval biologists.